Analisis Studi Kelayakan Bisnis pada Usaha Makanan Cimol Bojot Sawargi - Tiara Apriani; Dimas Muhammad Ramdani; Muhammad Raka Alfian; Perwito Perwito (Universitas Serambi Mekkah, 2025)
Cimol bojot is a popular snack with promising market potential. To develop a culinary business like cimol bojot, a business feasibility study is essential. This feasibility study involves an in-depth analysis of the proposed business plan. The purpose of this research is to assess the feasibility of the cimol bojot business in terms of finance, marketing, operations, and human resources. The research method used is qualitative descriptive analysis. Additionally, a literature review was conducted to gather relevant market information. The results of this study are expected to serve as an evaluation tool to improve and expand the cimol bojot business, as well as contribute positively to the culinary industry in Indonesia.